Application of artificial intelligence in online learning environments - Memari, Seyed Majid; Rafat, Abolfazl (Indonesian Journal of Multidisciplinary Science, 2025)
With the emergence of new technologies, especially artificial intelligence, a new perspective has been provided for improving the quality and accuracy of evaluation processes. Recent technological developments in various areas of human life, especially in the field of education and learning, have opened new perspectives for educational systems. In the meantime, artificial intelligence, as one of the most influential achievements of contemporary technology, has been able to find an important place in redefining the processes of education, evaluation, learning management and interaction between teachers and students. Elementary schools, which are known as the first formal institutions for the mental, emotional and social education of children, are now facing a wave of capabilities and challenges resulting from the introduction of artificial intelligence. This study examines the impact of using artificial intelligence (AI) on the level of interaction and participation of students in online learning environments.Given the increasing spread of e-learning and the need to increase the efficiency of educational processes, it is of particular importance to identify the factors affecting the improvement of the quality of learning and student engagement. The main objective of this study is to quantitatively and qualitatively evaluate the impact of AI-based tools, including educational chatbots and content recommendation systems, on the level of collaborative activities, feedback received, and students' sense of belonging in online learning platforms. The research method is a combination of quantitative (learning management system logs) and qualitative (interviews with students and instructors) data analysis.